«Sumus in via» El ser humano como realidad y como proyecto en el pensamiento de Xavier Zubiri - Valentín Navarro Caro (Claridades: Revista de Filosofía)
The question of the human being has been a constant in the history of thought, but specialists in the subject do not agree on what it is that qualifies human reality. The present article contributes to the open debate in philosophical anthropology since the thought of Xavier Zubiri. Basically attending to the work of this author, it presents what, in his opinion, constitutes what is specific to the human being, which is to be an open and projective reality. From here, important consequences are drawn for the present time.